Si incorporated Pt nanoparticles on TixSi1-xO2 support: Photo-thermal CO2 reduction. Issue 47 (May 2021) - Yadav, Rajkumar; Verma, Vikas; Mishra, Ankit; Pal, Neeraj; Khan, Azeem; Sinha, Anil Kumar
Graphical abstract: Highlights: Pt nanoparticles (NPs) incorporated with Si sites were synthesized on mesoporous TixSi1-xO2 support using a novel synthetic strategy. The DFT study showed incorporation of Si sites decreased the potential gap between the conduction band of titania and the Fermi level of Pt NPs. The effect of Si sites in Pt NPs size was studied on activity and selectivity for photo-thermochemical reduction of CO2 into CO, methanol, and CH4. PtSi /Ti0.76 Si0.24 O2 catalyst showed the highest methanol (1.38 mol%) and methane (0.46 mol%) production with 3.09 mol% CO2 conversion. Abstract: There is a great interest in solar fuels from CO2, the main greenhouse gas. The CO2 conversion suffers from major challenges of high temperature and pressure, low solar utilization, and low CO2 conversion. Pt nanoparticles are one of the best co-catalysts in a photochemical reaction where they play an important role in the activity and selectivity of reactions. Pt nanoparticles (NPs) incorporated with Si sites were synthesized on mesoporous Tix Si1-x O2 support. Incorporation of Si sites decreased the Pt NPs size. The first principle study showed incorporation of Si sites decreased the potential gap between the conduction band of titania and the Fermi level of Pt NPs, resulting in higher interaction. The incorporation of Si sites in Pt NPs showed higher adsorption energy for bent CO2 thereby higher CO2 activation as compared to linear CO2 on the undoped Pt NPs. The effect of Si sites on Pt NPs size was studied for activity and selectivity of photo-thermochemical CO2 reduction into CO, methanol, and CH4 . The catalyst with 24 mol% Si showed higher selectivity for methanol as compared to catalysts with 18 and 28 mol% Si. Incorporation of Si sites greatly influenced the Pt NPs size, metal-support interaction, and CO2 reduction efficiency. The effects of UV light, visible light, and GHSV rate on product profiles were studied. PtSi /Ti0.76 Si0.24 O2 catalyst showed the highest methanol and methane production (1.38 mol% and 0.46 mol%, respectively) with 3.09 mol% CO2 conversion.